Identification of Echinococcus Granulosus Genotype in Iraqi's Sheep by Using Nd1 Gene - MJ Muhaidi (Journal of Global Pharma Technology, 2018)
Hydatid Cysts were obtained from 15 sheep from hepatic, pulmonary, spleen, heart, and peritoneal cavity, between December 2014 and October 2015. Hydatid cysts (protoscoleces) were used for DNA extraction by using mechanical grinder. The purification of mt DNA was done by (promega kit, USA). The mitochondrial NADH dehydrogenase subunit 1 (ND1) genes was applied as aim for amplification by using polymerase chain reaction (PCR), all of 15 hydatid cysts yielded amplification products.PCR product for NADH1 800 bp. The PCR products had been purified and fractional sequences were produced. The sequences obtained were found to align with corresponding region for ND1 gene in the Gene Bank nucleotide database confirming to genotype of sheep strain (G1) in Iraq, Phylogenetic dissection of fractional sequence datum from ND1 gene for obtained Phylogenetic tree. G1 genotype was the majority widespread taxon and the genuine provenance of infection for Iraqi’s sheep. All of 15 specimens were G1 strain (sheep strain) according to the fractional sequences of NADH dehydrogenase 1 (ND1).Keywords: G1 strain, Hydatid cyst, ND1 gene, sheep, Sequences.